Percy gets upset - Murphy, Stuart J., 1942- (Watertown, MA : Charlesbridge, 2011)
Mommy and Daddy help their son calm down and feel better when situations during the day make him angry.
Kirkus Review
Kirkus Review, January 2011
1.6
Preschool
Preschool
Keywords: Anger -- Juvenile fiction; Animals -- Juvenile fiction; Emotions -- Juvenile fiction; Giraffe -- Juvenile fiction; Anger -- Fiction; Animals -- Fiction; Emotions -- Fiction; Giraffe -- Fiction; Anger -- Fiction; Animals -- Fiction; Emotions -- Fiction; Giraffes -- Fiction; Picture books for children